Blood-Brain Delivery Methods Using Nanotechnology - Daniel Mihai Teleanu; Cristina Chircov; Alexandru Mihai Grumezescu; Adrian Volceanov; Raluca Ioana Teleanu (MDPI AG, 2018)
Pathologies of the brain, of which brain cancer, Alzheimer’s disease, Parkinson’s disease, stroke, and multiple sclerosis, are some of the most prevalent, and that presently are poorly treated due to the difficulties associated with drug development, administration, and targeting to the brain. The existence of the blood-brain barrier, a selective permeability system which acts as a local gateway against circulating foreign substances, represents the key challenge for the delivery of therapeutic agents to the brain. However, the development of nanotechnology-based approaches for brain delivery, such as nanoparticles, liposomes, dendrimers, micelles, and carbon nanotubes, might be the solution for improved brain therapies.